The Transactions Theory of the Demand for Money: A Reconsideration - Clower, Robert W.; Howitt, Peter W. (Journal of Political Economy, 1978)
This paper deals with a class of models of the demand for money that includes the Baumol-Tobin and other inventory-theoretic models as special cases. Among other things, the analysis shows that many supposedly robust comparative-statics propositions derived by earlier writers do not survive even modest generalization. More generally, the results of the paper strongly reinforce other recent research in indicating the need for a wholesale reconstruction of the microfoundations of contemporary monetary theory.